2015
DOI: 10.1038/srep13721
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR-223 Contributes to Mesenchymal Stem Cell-Elicited Cardioprotection in Polymicrobial Sepsis

Abstract: Mesenchymal stem cells (MSCs) have been shown to elicit cardio-protective effects in sepsis. However, the underlying mechanism remains obscure. While recent studies have indicated that miR-223 is highly enriched in MSC-derived exosomes, whether exosomal miR-223 contributes to MSC-mediated cardio-protection in sepsis is unknown. In this study, loss-of-function approach was utilized, and sepsis was induced by cecal ligation and puncture (CLP). We observed that injection of miR-223-KO MSCs at 1 h post-CLP did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
220
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(237 citation statements)
references
References 47 publications
(126 reference statements)
4
220
1
Order By: Relevance
“…An example of this type of study would be the injection of extracellular vesicles isolated from either WT or miR-223-deficient mice into septic mice. With this technique, the authors were able to precisely determine how extracellular vesicle miR-223 impact the host response to sepsis (68). Here, had they been available and viable, the ideal control would have been NDMPs isolated from PS-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this type of study would be the injection of extracellular vesicles isolated from either WT or miR-223-deficient mice into septic mice. With this technique, the authors were able to precisely determine how extracellular vesicle miR-223 impact the host response to sepsis (68). Here, had they been available and viable, the ideal control would have been NDMPs isolated from PS-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…This novel mechanism of miRNA transfer constitutes an important element of intracellular communication. Very recently, our lab has reported that stem cell-derived exosomal miR-223 significantly suppressed the production of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) by targeting Sema3A and STAT3 in macrophages of septic model (10). Similarly, another study showed that miR-155 and miR-146a, present in dendritic cell-derived exosomes, were passed between immune cells in vivo (11).…”
Section: Mirna Biogenesis and Mechanism Of Actionmentioning
confidence: 99%
“…The mechanism for MSC-induced protection is unknown; however, it has been demonstrated that MSCs release exosomes during sepsis that harbor miR-223 which is cardioprotective in the CLP-induced sepsis model [100]. This effect may be related to the anti-inflammatory effects of miR-223 which reduces the expression of proinflammatory cytokines.…”
Section: Mitochondrial Dysfunction Can Lead To Permanent Muscle Loss mentioning
confidence: 99%